The language acquisition process for children with autistic spectrum disorder: review article (Research, Society and Development, 2021)
Objective: To present a survey of scientific publications on the language acquisition of children with autism spectrum disorder, addressing the interventions used by speech therapists. Method: This research is a review of critical literature, of qualitative analysis, which aims to systematize results of articles, theses and results of research carried out with the process of language acquisition in individuals with Autism Spectrum Disorder and the speech therapist as a professional relevant in this process. Results: It was observed that the studies found complete several aspects in the process of language acquisition, strategies and practices that favor this process, school and professionals with interventions based on the uniqueness of each subject, favoring the social insertion of autistic people in communicative and conversational. Conclusion: The articles and theses presented contribute to present relevant scores on the language acquisition process in autistic people.